Forums for Parents of Young Children: Parents’ Online Conversations in Israel and France - Chen, Pascale; Aram, Dorit; Tannenbau, Michal (International Journal about Parents in Education, 2023)
This paper compares discussions in online forums on the parenting of young children in France and Israel through a cross-national perspective. We mapped and coded the activity in four major forums on early-age parenting, two in each country, during two months (N= 3,244 posts). Analysis of the posts revealed that, overall, parents in both countries focused more on children than on parenting issues and were mostly interested in their children’s educational settings. French participants discussed cognitive and developmental issues more than Israelis parents, whereas Israeli parents were more concerned with social-emotional development and parenting issues than the French participants. Results are discussed from a cross-national perspective, and practical implications are suggested, relating to a safe and empowering virtual space where parents and professionals assist parents of young children from different cultural backgrounds to adjust to their particular needs, interests and expectations.